Analysis of nonlinear vibration characteristics of dual-rotor system under bearing misalignment-rub-coupling fault - NIE YanChun; YU JianHui; ZHANG LeiKe; WANG XueNi; ZHANG JinJian; TANG HuaLin (Jixie qiangdu)
In order to reveal the vibration characteristics of fault rotor systems caused by the bearing misalignment, the expression of the rotor deflection displacement under the bearing misalignment was derived through the coordinate transformation relation. On this basis, the dynamic model of the double disk rotor system with the coupled bearing misalignment-rub-impact fault, considering the influence of external excitation including the rub-impact force and the oil film force was established. The effects of rotational speed and mass eccentricity on the dynamic response of the system were studied by means of the numerical method. The results show that the bearing misalignment fault can increase the possibility of rub-impact, worsen the shafting vibration and magnify the unsteady motion range of system. Although the addition of misalignment can delay the instability movement induced by parameter changes to a certain extent, the enlargement of amplitude is contrary to the safe operation goal for system, therefore, the necessary measures should be taken to control the bearing misalignment fault. The relevant conclusions can provide useful references for the vibration state identification and the stability analysis of rotor bearing systems.